Contemporary digital sociology in search of meaning-making models: the proper and the actual. Review on articles from the research handbook of digital sociology edited by J. Skopek. Part I - E. V. Andrianova; V. A. Davydenko; A. I. Rozmanov (Цифровая социология, 2025)
The review of the research handbook on digital sociology, edited by J. Skopek, provides a critical analysis of this field, encompassing studies on digital society, digital life, digital engagement, digital scientific and technological changes, and their consequences, alongside many related pressing issues. The book is both empirically oriented and fundamentally robust, maintaining its analytical and scientific depth. The purpose of the review is to present the key ideas of all 25 chapters of the handbook, which, due to editorial requirements, we must present in two parts. The handbook is structured into 5 sections reflecting key areas of digital sociology: social theory and the internet in everyday life, research of digital society, analysis of digital life and online interactions, digital participation and inequality, and consequences of digital technological changes. Each chapter is supported by extensive academic literature, both classical and modern, mostly published in recent years, which significantly expands the radius of the proposed subject contexts. The first part of this review presents the key ideas of 15 chapters, focusing on the foundational components of social  theory and their connections to the internet in daily life, digital  technologies for surveys and data processing, the significance  of mobile devices, big data, machine learning, agent-based  models of social phenomena, inclusive digital focus groups, social networking sites in professional contexts, online dating, partner selection based on digital information, the use of digital approaches in online markets, the application of YouTube in social sciences, and automated image analysis. A distinctive feature of the review is its exploration of the intersection between the digital and social spheres, framed as a contradiction between the proper (computer sciences) and the actual (social sciences), reflecting the search for meaning in communication and action within digital and social spaces.